'Warga emas' enrich classes at varsity - Abd Razak, Dzulkifli (2008)
ONE of the greatest rewards of an educator is to see the students pass out after completing their studies. Hence, during each convocation, the entire university community celebrates not only the students' success, but also the extended support that made these achievements possible. From time to time, there are occasions when the convocation draws an even more special meaning. In one such case, the first student with cerebral palsy graduated with flying colours, earning her the privilege of the coveted Chancellor's Gold Medal at Universiti Sains Malaysia. USM recorded another historic moment in its most recent convocation. This time, a group of six from the pioneer batch of warga emas (senior citizen) students walked up to the stage to receive their scrolls from the chancellor.